PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 060879 MEDAN TIMUR TA 2025/2026 - Simanjuntak, Aulia; Husna Parluhutan Tambunan; Wildansyah Lubis; Nurhairani; Apiek Gandamana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of the Make a Match cooperative learning model assisted by flashcard media on the IPAS learning outcomes of Grade V students at SDN 060879 Medan Timur on the topic What Is the Shape of Indonesia? in the 2025/2026 academic year. The study employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The research population consisted of all Grade V students divided into two classes, namely class V-A as the experimental group and class V-B as the control group, each consisting of 30 students. The research instrument was a learning outcomes test in the form of pre-test and post-test consisting of 20 multiple-choice questions. The results of data analysis showed that the average post-test score of the experimental class was 73.67, which was higher than that of the control class at 61.33. The t-test results indicated a of 4.121 and a value of 2.001 at a significance level of 0.05, leading to the rejection of and acceptance of Therefore, it can be concluded that the application of the Make a Match cooperative learning model assisted by flashcard media has a significant effect on the IPAS learning outcomes of Grade V students.